The Incidence and Characteristics of Perinatal Stroke in Beijing: A Multicenter Study - Qianqian Xia; Zhao Yang; Yao Xie; Ying Zhu; Zixin Yang; Mingyan Hei; Yingxue Ding; Weijing Kong; Limin Kang; Shengnan Yang; Yabo Mei; Zhichun Feng; et al. (Frontiers Media S.A., 2022)
ObjectiveTo assess the incidence, risk factors, and clinical characteristics of perinatal stroke in Beijing.MethodsThis multicenter prospective study included all the live births from 17 representative maternal delivery hospitals in Beijing from March 1, 2019 to February 29, 2020. Neonates with a stroke were assigned to the study group. Clinical data, including general information, clinical manifestations, and risk factors, were collected. Up until 18 months after birth, neonates were routinely assessed according to the Ages and Stages Questionnaire (ASQ) and/or the Bayley scale. Statistical analysis was done using the chi-squared, t-tests, and logistic regression analysis using SPSS version 26.0.OutcomesIn total, 27 cases were identified and the incidence of perinatal stroke in Beijing was 1/2,660 live births, including 1/5,985 for ischemic stroke and 1/4,788 for hemorrhagic stroke. Seventeen cases (62.96%) of acute symptomatic stroke and convulsions within 72 h (10 cases, 37.04%) were the most common presentations. Ten patients showed no neurological symptoms and were found to have had a stroke through routine cranial ultrasonography after being hospitalized for non-neurological diseases. The risk factors include primiparity, placental or uterine abruption/acute chorioamnionitis, intrauterine distress, asphyxia, and severe infection. In the study group, 11.1% (3/27) of patients had adverse neurodevelopmental outcomes. The patients in the study group had lower scores for the ASQ than those in the control group in the communication, gross, and fine motor dimensions.ConclusionThe incidence of perinatal stroke in Beijing was consistent with that in other countries. Routine neuroimaging of infants with risk factors may enable identification of asymptomatic strokes in more patients. Patients who have suffered from a stroke may have neurological sequelae; therefore, early detection, treatment, and regular follow-ups are beneficial for improving their recovery outcomes.